REDUCTION IN CHILD SUPPORT FOR EXTENDED VISITATION IN UTAH: EXTRA-CREDIT OR FINANCIAL TIME-OUT? (Journal of Law and Family Studies; Vol 11 No 1 (2008))
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; mso-bidi-font-size:11.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} As more families face the realities of divorce, the court system is increasingly asked to make decisions regarding the best interests of the children involved.   These decisions are mostly related to child support and visitation. By the 1970s, in almost all states, child support awards were determined on a case-by-case basis by a single judge. “This [case-by-case] system led to grave inequities and dissatisfaction . . . because people in identical circumstances were treated very differently.” In 1984, in an attempt to provide a more equal justice, the U.S. Congress required all states to “develop numerical child support guidelines.”